Cinnamomum Adulteration: Scope, Detection Methodologies, Health Implications, and Regulatory Challenges A Global Review - Raymond R. Tjandrawinata (Riviera Publishing, 2026)
Cinnamon is among the world’s most economically significant spices, yet the genus Cinnamomum is one of the most frequently adulterated food commodity groups due to price differentials between premium Ceylon cinnamon and Cassia varieties, compounded by the visual indistinguishability of powdered products. This review—Cinnamomum Adulteration: Scope, Detection Methodologies, Health Implications, and Regulatory Challenges A Global Review—provides a comprehensive analysis of Cinnamomum adulteration encompassing botanical differentiation, adulteration typology, detection methodologies, health implications, and global regulatory architecture, with special attention to C. burmannii’s ambiguous regulatory status. It synthesizes peer-reviewed literature, regulatory documents, and international standards from 2004 to 2025, systematically analyzing detection platforms spanning classical, spectroscopic, chromatographic, and molecular DNA-based methods. The 2025 EU JRC study analyzing 104 commercial samples found that over 66% failed quality standards or exceeded coumarin limits, with species substitution confirmed in 9% of Ceylon-labeled products. Advanced detection methods include Bar-HRM, qPCR, NIR, EDXRF, and HPLC-DAD, enabling comprehensive authentication across multiple adulteration types. Health risks center on coumarin hepatotoxicity (Cassia: up to 12.18 mg/g; C. verum: 0.005–0.090 mg/g), heavy metal toxicity, and allergen mislabeling. Cinnamomum adulteration requires a species-specific, risk-based authentication framework supported by regulatory harmonization among ISO, Codex Alimentarius, and national agencies. The Codex Alimentarius Commission’s 2024 decision to initiate cinnamon standard development creates a policy window for action. Future priorities include harmonized coumarin limits, mandatory species labeling, heavy metal surveillance, and capacity building for molecular authentication in producing countries.